Validation of the Sexual Sensation Seeking Scale in Spanish Samples. Issue 4 (4th July 2018) - Santos-Iglesias, Pablo; Moyano, Nieves; Castro, Angel; Granados, M. Reina; Sierra, Juan Carlos
ABSTRACT: The aim of this study was to validate the Sexual Sensation Seeking Scale (SSSS; Kalichman, 2011) in Spanish samples. Two independent studies were conducted. In Study 1, we examined the factor structure of the SSSS in a sample of 1, 272 heterosexual undergraduate students (40.0% men, 60.0% women). Results revealed a 2-factor structure. Factor 1 was related to physical sexual sensations and risky sexual behaviors and Factor 2 was related to exploratory or novel sex. A confirmatory factor analysis confirmed this factor structure in a sample of 373 community adults (33.8% men, 66.2% women). Two items were deleted, resulting in a final version composed of 8 items. This version showed good test–retest reliability and evidence of its concurrent validity. In Study 2, the factor structure was further confirmed in a sample of 1, 596 university students (28.8% men, 71.2% women). More evidence of construct validity was provided, which revealed that higher levels of sexual sensation seeking were associated with more frequent sexual risk behaviors and poorer sexual health. Internal consistency reliability did not reach acceptable levels on all of the subscales. Results suggest that, although it has been used before, this scale needs a revision before its use in Spanish-speaking contexts.